Anti-IH Related Hemolytic Reaction in a Sickle Cell Patient and Further Management While Avoiding Transfusion. (28th October 2020) - Yurtsever, N; Wilson-Sandberg, K; Dikeman, J; Louie, J; Fomani, K
Abstract: Introduction/Objective: H antigen is a precursor for A and B antigens and is mostly converted except for the O blood group, which has the highest amount of H antigen. I is present on all adult RBCs. Anti-IH is usually an IgM antibody active at cold temperatures, and rarely demonstrates a wide thermal amplitude and can cause a significant hemolytic transfusion reaction. Methods: Data was collected from patient information and transfusion management systems. Results: 38 year old female with sickle cell disease presented to the emergency room with dizziness, tachypnea and Hgb: 5.9 g/dl Hct:19.1%. Upon further review, patient chart showed that she had received an emergency RBC exchange transfusion 21 days prior to this admission for acute chest syndrome. She was B positive. The units for RBC exchange consisted of 5 group B and 1 group O units and an additional 1 group O unit later. All RBC units were matched for her phenotype; Rh, K, Duffy & Kidd, except anti-S which was ruled out. At the time of discharge, Hgb was 9.3 g/dl and Hct was 27.7%. The drop in Hgb between discharge and the present admission prompted a suspicion for delayed hemolytic reaction/hyperhemolysis. The sample sent to the local Reference Laboratory came back as follows: DAT/Coombs Positive, DAT C3 positive; positive for cold auto-anti-IH antibody. A thermal amplitude test indicated that the anti-IH was reactive at 30 C and therefore had the potential to be of clinical significance. Her Hgb continued to drop and 3 days later Hb=3.7 g/dl with instructions not to transfuse unless clinically emergent. With treatment of IVIG and steroids, reducing further blood draws and monitoring the patient for clinical symptoms only, her Hgb/Hct started to rise and the patient was discharged 4 days later with Hgb: 6.4 g/dl, and no symptoms of anemia. Conclusion: Our case study is important in two ways: Firstly, it raises awareness of the severity of a cold autoantibody, i.e. anti-IH, with a wide thermal amplitude. Specifically, in this case, our attempt to provide phenotypically similar RBCs resulted in the destruction of all the type O donor cells as well as some of the B donor cells. Secondly, even with Hgb counts as low as 3.7, treating the patient and not the number proved to be better clinical practice. In conclusion, a good monitoring protocol for sickle cell patients is required to transfuse less and avoid serious complications.